Prawa pacjenta w dobie pandemii COVID-19 – wybrane zagadnienia - Kulikowska-Kulesza, Justyna E. (Studia Prawa Publicznego, 2023)
The SARS-CoV-2 coronavirus pandemic has changed how almost every sphere of our lives functions. Its greatest impact can be seen in the functioning of the health care sector, whose task was not only to care for the sick or people suspected of infection, but also to take all measures to prevent the spread of infections. The imposition of a state of epidemic threat in Poland, and then the state of epidemic, provided a basis for imposing a number of restrictions that had a significant impact on the realisation of patients’ fundamental rights. The purpose of the considerations is to present and analyse the limitations of selected patient rights during the SARSCoV-2 pandemic. This article first presents issues related to patient rights in genere, emphasizing their importance for the proper functioning of the health care system in the country. Next, the limitations of selected patient rights, which unquestionably occurred in the era of COVID-19, are presented. It is shown that the rights indicated were not only limited, and sometimes even excluded. The article also presents an analysis of the annual reports of the Patients’ Rights Ombudsman, which in their content confirms the great increase in the number of violations of patient rights in the period of SARS-CoV-2 pandemic. Consequently, this resulted in a far-reaching negative impact on the perception of the health care system in our country.